Exosomes originating from MSCs stimulated with TGF‐β and IFN‐γ promote Treg differentiation. Issue 9 (11th April 2018) - Zhang, Qingyi; Fu, Lin; Liang, Yahui; Guo, Zikuan; Wang, Lisheng; Ma, Cong; Wang, Hengxiang
Abstract : Mesenchymal stem cells (MSCs) have been approved as a cellular drug for the treatment of a variety of immune‐related diseases by the government of many countries'. Previous investigations, including ours, have shown that exosomes secreted by MSCs (MSC‐ex) are one of the main factors responsible for the therapeutic effect of MSCs. However, the immune modulation activities and the contents of MSC‐ex derived from cells under different incubation conditions differ dramatically. Therefore, the optimal way to ensure effectiveness is by identifying and preparing MSC‐ex with confirmed potent immunosuppressive activity. The aim of this study was to investigate and analyze the composition and function of MSC‐ex secreted by MSCs stimulated by different cytokines to obtain exosomes with more potent immunosuppressive activity. To achieve this aim, umbilical cord‐derived MSCs were treated with PBS, TGF‐β, IFN‐γ, or TGF‐β plus IFN‐γ for 72 hr. Then, exosomes were isolated from the culture supernatants. Common exosome markers, such as CD9, CD63, and CD81, were detected and analyzed by FCM. At the same time, the TGF‐β, IFN‐γ, IDO, and IL‐10 content in exosomes was detected, and the influence of exosmes from defferent groups on the induction of mononuclear cell transformation into Tregs was analyzed via FCM. Our results show that the TGF‐β combined with IFN‐γ exosome group more effectively promoted the transformation of mononuclear cells to Tregs, and the analysis showed that IDO may play an important role. This study might provide a novel strategy to treat GVHD as well as other immune‐associated disorders. Abstract : MSC‐ex secreted by MSCs stimulated with cytokines of TGF‐βplus IFN‐γcan promote PBMCs to differentiate into Tregs, which may be related with a variety of increasing cytokines, and IDO plays an important role in the process.